Enantioselective Protonation of Silyl Enol Ethers Catalyzed by a Chiral Pentacarboxycyclopentadiene-Based Brønsted Acid - Li, Jun; An, Shaoyu; Yuan, Chao; Li, Pingfan (Synlett, 2019)
The enantioselective protonation of silyl enol ethers was realized in the presence of a pentacarboxycyclopenta-1,3-diene-based chiral Brønsted acid catalyst with water as an achiral proton source to give the corresponding α-aryl ketones in good yields and up to 75% ee.
Keywords: protonation; Brønsted acids; asymmetric catalysis; organocatalysis; carbonyl compounds; silyl enol ethers